Bridging Gaps in Reproductive Health Care in Egypt through Private Sector Involvement - Cole, Andy; Afifi, Mohamed; Salah, Reem (World Bank, 2012)
Illustrates the reproductive health project Takamol which seeks to increase the availability and quality of reproductive health services.